Analisis Sektor Ekonomi Dalam Struktur Perekonomian Kabupaten Banggai Kepulauan: Analysis of the Economic Sector in the Economic Structure of Banggai Islands Regency - Taufik Bidullah (Jurnal Ilmiah Produktif, 2022)
This study aims to determine the rate of growth of economic sectors, the factors that influence them, and the economic sectors that are the basis and non-base sectors in the economic structure of the Banggai Islands Regency. This study used secondary data in the form of GRDP at constant prices in 2000, Banggai Islands Regency and Central Sulawesi Province as a comparison with the time series during the 2009-2013 period, carried out calculations and analysis using economic growth analysis techniques, Location Quotient (LQ) and Shift analysis. Share. The study results indicate that by sector, the transportation and communication sector is the sector that achieves the highest economic growth rate compared to other economic sectors. The growth rate of these economic sectors is influenced by the potential comparative advantage available in these economic sectors. There are basic sectors, namely the agricultural and trade sectors, hotels and restaurants. Meanwhile, those classified as non-basic sectors are the manufacturing industry sector, the transportation and communication sector, the financial sector, leasing and company services, the excavation sector, the electricity and clean water sector, the building sector, and the services sector